1954
DOI: 10.1021/ja01637a092
|View full text |Cite
|
Sign up to set email alerts
|

RELATIVE IMPORTANCE OF STERIC AND INDUCTIVE EFFECTS IN SN2 DISPLACEMENT REACTIONS

Abstract: Table I Exchange Reactions Catalyzed by the P Enzyme In experiment A, the complete system contained 1.3 µ . succinyl CoA, 50 µ . TRIS pH 7.4, 5 µ . C14-succinate, 0.17 mg. enzyme protein (5.2 units), 5µ . P04 and 5µ . MgClj; 2.5 µ . ADP added when indicated; final volume 1.0 ml.; incubated 6 minutes at 20°. After incubation, NH2OH was added and the succinohydroxamic acid separated from succinate by chromatography on Dowex 1. About 0.90-1.17 µ .of succinohydroxamic acid was isolated from the column.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1956
1956
1985
1985

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The rate measurements of Acree and Shadinger (2) did not give good second-order rate constants for the reaction of tert-butyl iodide with the sodium salt of l-phenyl-3-thiourazole (X) in 50 per cent aqueous alcohol; this reaction was doubtless complicated by concurrent solvolysis. Conant and Hussey (157) found that tert-butyl chloride is more reactive than isopropyl chloride towards potassium iodide in acetone, but this result is contradicted by more recent work (440,521).…”
Section: Structural Egects In the Substratementioning
confidence: 96%
See 1 more Smart Citation
“…The rate measurements of Acree and Shadinger (2) did not give good second-order rate constants for the reaction of tert-butyl iodide with the sodium salt of l-phenyl-3-thiourazole (X) in 50 per cent aqueous alcohol; this reaction was doubtless complicated by concurrent solvolysis. Conant and Hussey (157) found that tert-butyl chloride is more reactive than isopropyl chloride towards potassium iodide in acetone, but this result is contradicted by more recent work (440,521).…”
Section: Structural Egects In the Substratementioning
confidence: 96%
“…On the other hand, the explanation has been offered that the greater effective bulk of increasing alkyl substitution sterically opposes the close approach of a nucleophilic reagent. This explanation is based on steric hindrance (115,233,235,380,449,521). The suggestion has also been made that the two effects are of comparable importance (198,222).…”
Section: Structural Egects In the Substratementioning
confidence: 99%
“…The relative reactivities of phenacyl chloride, 2-chloropropiophenone and a-chloroisobutyrophenone varied from 1 over 0.006 to 0.000 003. 21 As a matter of fact, -bromopropiophenone (15; Ar = Ph, R = Me, X = Br)22 and -chloropropiophenone (15; Ar = Ph, R = Me, X = Cl)23 are known to react with sodium methoxide in methanol to give 1,1-dimethoxy-1 -phenyl-2-propanol (17; Ar = Ph, R' = R = Me). The formation of -hydroxy acetal 17 was explained by carbonyl attack, epoxide (16) production, and subsequent opening by the nucleophile (Scheme VI).…”
Section: Discussionmentioning
confidence: 99%
“…The 4:1 ratio of 2b to 3b obtained at 0 °C was drastically changed into a 1:1 ratio when the substrate was dropped into a refluxing solution of sodium methoxide in methanol. It is clear that the rate of the reaction is very fast at temperatures above room temperature, but the distribution of products is determined by the temperature influence on the chemical behavior of a-chloro-a-methoxy-a-phenyl ketone 21 (R = R' = Me, X = Cl, Rx = R^= R3 = H). At higher temperature, the competition between solvolysis of the latter a-chloro ether and nucleophilic attack at the carbonyl function and subsequent epoxide formation will be shifted to the solvolysis pathway because of the predictable, more important influence on the carbon-halogen bond breaking of the -chloro ether.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation